Evaluación económica y financiera de una distribuidora de acero inoxidable estrategía full service en la ciudad de Bogotá (2017)
Stainless steel is a material present in each of the movable and immovable assets to which we make daily use of human beings, the importance and innocuousness of hygiene and sanitation are constant and of greater prolongation in the use of it, the strategy of marketing stainless steel with complementary products, allows to optimize the processes of diversification and obtain a portfolio of products that reduces the administrative procedures of consumers.